RADT-30. COPLANAR AND NON-COPLANAR VMAT ARC SETTING FOR GLIOBLASTOMA MULTIFORME – DOSIMETRIC AND RADIOBIOLOGICAL COMPARISONS - Moldoveanu, Vanessa (Neuro Oncol, 2020)
OBJECTIVES: To evaluate three different arc arrangements in glioblastoma multiforme (GBM) treatment planning. METHODS: Eighteen GBM patients were replanned by using one full arc (1FA), two full coplanar arcs (2FA), and three full non- coplanar arcs (3FA). Dose-volume histograms (DVHs) were used to calculate conformity (CI), homogeneity (HI) and gradient indices (GI), the dose received by 5% (D5%) and 95% (D95%) of the planning target volume (PTV) and maximum (Dmax) and minimum (Dmin) absorbed dose for organs at risk (OARs), including normal brain (brain excluding PTV). General equivalent uniform dose (gEUD) for both PTV and OARs and EUD based tumor control probability (TCP) and normal tissue control probability (NTCP) were calculated as radiobiological parameters. Monitor units (MUs) were also computed and compared. RESULTS: All three plans resulted in similar conformity, while 2FA resulted in a better homogeneity than 1FA (0.06vs. 0.07, p=0.007). 2FA vs. 1FA dose analysis for PTV revealed a lower D5% (61.28 vs. 61.37 Gy, p=0.014), a higher D95% (58.7 vs. 58.47 Gy, p=0.008) and a higher TCP (37.73 vs.37.38%, p=0.008). The utilization of 3FA did not significantly change the outcome of PTV but managed to decrease GI in comparison to both 1FA and 2FA (4.11 vs. 5.19 and 5.49, p< 0.05). Regarding NB, 1FA scored a higher Dmax than 2FA (62.32 vs. 61.98 Gy, p=0.005), while 3FA scored a higher Dmin than 1FA and 2FA (2.52 vs. 1.08 and 1.10 Gy, p< 0.05). No difference in NB NTCP was noted between techniques. Furthermore, 3FA yielded more MUs when compared to coplanar patters (566.74 vs. 486.78, p= 0.015 for 1FA and 495.98, p=0.019 for 2FA). CONCLUSION: Although all three approaches resulted in clinical admissible outcome, the utilization of complex non-coplanar arrangement resulted in a stepper dose fall off but did not improve PTV results and increased machine MUs.